Pengembangan Kulit Buah Kering Asam Kandis sebagai Herbal Medicine: Optimasi Formulasi Tablet Effervesen dan Uji Efeknya Terhadap Kenaikan Berat Badan dan Pola Makan Tikus - Lucida, Henny; Ben, Elfi Sahlan; Delita, Elfi (Jurnal Sains dan Teknologi Farmasi, 2012)
This paper reports an optimization technique of effervescent tablet formulation from the ethanolic extract of âasam kandisâ dried rinds (Garcinia cowa Roxb) and an assay of its reconstituted solution effect on ratâs body weight and feeding behavior. Formulation optimization was done by factorial design of 2 factors (extract concentration; composition of tablet disintegrant) and 3 levels. Nine formulas (FI â FIX) were prepared and subjected to evaluations including granuleâs physicochemical and tabletâs pharmaceutical properties. The best formula was then chosen and given orally to 4 groups of rats: that was given standard food, high fat diet, high fat diet with reconstituted tablet 250 mg and high fat diet with reconstituted tablet 500 mg respectively. All groups were given 10 g of standard food every day for 10 days followed by high fat diet for the next 22 days. Two treatment groups were given reconstituted tablet at day 11th. The amount of food consumed by each group was weighed and ratâs body weight was measured. The optimization technique showed that both factors influenced the physicochemical properties of granules and the pharmaceutical properties of tablets significantly (p < 0.05). FV (extract concentration 500 mg, disintegrant: sodium bicarbonat 500 mg + citric acid 200 mg + tartaric acid 200mg) was chosen as the best.  Results showed that administration of reconstituted tablet FV to rats increased the bodyweight of the treated groups for the first week which then decreased during the next 3 week observation, while the body weight of control group kept increasing. Reconstituted tablet at dose 500 mg significantly influenced ratâs bodyweight and the feeding behavior (p<0.05). The group given reconstituted tablet 500 mg had the lightest body weight and consumed the least food during 3 weeks observation.